Efficacy, safety, and tolerability of a 24-month treatment regimen including delamanid in a child with extensively drug-resistant tuberculosis: A case report and review of the literature. Issue 46 (November 2016) - Esposito, Susanna; Bosis, Samantha; Tadolini, Marina; Bianchini, Sonia; Migliori, Giovanni Battista; Principi, Nicola
Abstract: Rational: Multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) are emerging problems in several countries. These infections require long and expensive treatment regimens. Recently, 2 new drugs, bedaquiline and delamanid, have been approved in several countries for use in adults with severe, difficult-to-treat MDR-TB, and it has been suggested that they could also be administered to children with MDR-TB and limited treatment options. However, no study has been completed on their efficacy. Patient concerns: This report describes a 12-year-old child with XDR-TB who was cured after a 24-month therapy regimen, which included delamanid. Diagnoses: The patient showed progressive clinical deterioration after 5 months of treatment with the majority of anti-TB drugs available on the market. Interventions: After unsuccessfull treatment with several anti-TB drugs for 5 months, he was treated with a regimen including for 24 months. Outcomes: Direct smear microscopy of the gastric aspirates and gastric aspirate cultures for Mycobacterium tuberculosis became negative after only 1 week and remained persistently negative. During the 24-month treatment, all blood test results remained within the normal range, no adverse events were reported, and corrected QT interval was always normal. A clinical and laboratory control was performed 3 months after discontinuation of delamanid, and the other drugs did not reveal any modification of both general conditions as well as laboratory and radiological findings. The patient was considered cured. Lessons: The positive outcome associated with the favorable safety and tolerability profile showed that long-term therapy with delamanid can significantly contribute to treating apparently hopeless XDR-TB cases in children.